Studi Eksperimen Pengaruh Penggunaan Koh Terhadap Performa Generator HHO Tipe Dry Cell Dengan Dimensi Setiap Plat 3.046,59 Mm2 - R Nofriyandi (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
This research is aimed to analyze efficiency and produced HHO gas from HHO type dry cell generator. The experimental apparatus of a generator consists of 4 cells and four neutral plates for each cell is produced. The generator plate used in the electrolysis process has dimension 30.29 mm2. The total area of plate is 70 mm x 70 mm and it has a single hole with diameter 12 mm located in the middle of the plate. To collect the data, the generator has been operated for 2 hours. The efficiency of the generator is evaluated by addition of 5, 7 and 9 gram KOH into the cell. It was shown from the experiment that, the average of HHO gas resulting from 5 gram KOH is 6.45 ml/s with efficiency 89.39%.  Meanwhile, for 7 and 9 gram KOH, the average HHO gas are 9.31 ml/s and 12.92 ml with efficiency 72.29% and 83.49%, respectively.